PERANCANGAN APLIKASI E-COMMERCE UNTUK MENINGKATKAN EFISIENSI OPERASIONAL SISTEM PENJUALAN UMKM - Dian Resha Agustina; Sonni Tian Dhora; Samuel Godlife (Universitas Putera Batam, 2025)
This research aims to design and develop an e-commerce application using the Flutter framework and Dart programming language, targeted at empowering SMEs under the guidance of Rumah BUMN Bandar Lampung. The methodology employed is the Waterfall model, allowing for systematic and structured application development. The research results indicate that this application can add products, manage stock, process transactions, and facilitate consumer access, ultimately enhancing the operational efficiency of the SMEs' sales system. Application testing showed satisfactory results with performance meeting expectations. The study recommends the development of additional features such as sales analytics, user interface optimization, and enhanced application security.